The Impact of Social Media on the Formation of Religious Patterns Among Millennial Students in Ponorogo - Muslim, Abu; Choiri, Moh. Miftachul; Sham Kamis, Abu Mohd (IAIN Ponorogo, 2024)
This study investigates the impact of social media, specifically YouTube, on the religious practices of millennial students in Ponorogo. The increasing reliance of millennials on YouTube as a primary source of religious content indicates a shift from traditional religious education to digital platforms, driven by YouTube’s diverse content offerings. The research aims to explore this phenomenon by employing a qualitative approach with a descriptive-analytical method. Using the Technology Acceptance Model (TAM), the study examines the factors influencing the acceptance and use of YouTube for religious learning. At the same time, Social Construction Theory was applied to understand how social interactions and media influence students' religious practices. The findings reveal that YouTube facilitates religious engagement without time or location limitations, offering a flexible, innovative platform for spreading religious messages. Millennial students in Ponorogo construct their religious practices through externalization, objectivation, and internalization, with YouTube as a central medium. This study presents new insights into the shift in religious patterns among millennials, where YouTube content broadens their religious understanding and influences beliefs, encompassing both moderate and conservative perspectives.